Characterization of marine bacteria isolates GaN 2 and RaN 2 from Papuma Coastal, Jember - Wathon, Syubbanul; Senjarini, Kartika; Oktarianti, Rike; Hasanah, Fitrianti Milhatul; Oktavia, Melinda Dwi Putri; Puspitasari, Endah; Labes, Antje (Jurnal Biolokus : Jurnal Penelitian Pendidikan Biologi dan Biologi, 2025)
The exploration of secondary metabolites for various human needs has now extended to aquatic environments. The fluctuating and dynamic nature of aquatic environments can stimulate marine bacteria to adapt by producing secondary metabolites. The diversity of marine bacteria has become increasingly promising as a target for obtaining various potential secondary metabolites. This study aims to isolate potential marine bacteria that produce secondary metabolites from the Papuma Beach area in Jember. Marine bacterial characterization can be carried out through morphological and molecular approaches. In this study, bacterial isolates were collected from marine algae at aquatic sites. Bacteria were isolated from the algae using the spread plate and streak plate methods on nutrient agar dissolved in artificial seawater as the medium until single colonies were obtained. Morphological characterization of the single colonies was conducted by observing colony shape and color, as well as performing Gram staining. Molecular characterization of selected single colonies was performed by amplifying the 16S rDNA as a bacterial molecular marker. The results of this study showed that marine bacteria that grew well and remained stable on artificial media were successfully isolated from green and red algae samples, labeled GaN 2 and RaN 2, respectively. The GaN 2 bacterial isolate was identified as Fictibacillus barbaricus strain SQ5-4, while the RaN 2 bacterial isolate was identified as Bacillus altitudinis strain 41KF2bT.26. According to previous studies, Fictibacillus barbaricus is known to have potential as a bioremediation agent, while Bacillus altitudinis has potential applications as an antitumor, antimicrobial, and antioxidant-producing agent.